A Series on Diseases in the Florida Vegetable Garden: Cantaloupe - Pamela Roberts; Rosa Muchovej; Tom Kucharek; Ken Pernezny; Timur Momol (EDIS)
PP-236, a 5-page illustrated fact sheet by Pam Roberts, Rosa Muchovej, Tom Kucharek, Ken Pernezny, and Timur Momol, is one of a series on Diseases in the Florida Vegetable Garden. It describes disease-causing organisms, specific common cantaloupe diseases, and some tips on disease prevention for the Florida gardener. Published by the UF Department of Plant Pathology, July 2007.